2013
DOI: 10.1016/j.labeco.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Do reductions of standard hours affect employment transitions?: Evidence from Chile

Rafael Sánchez

Abstract: This study exploits the reduction of weekly working hours from 48 to 45 occured in Chile in January 2005. We use this pure and exogenous policy change to identify the employment e¤ects of such a policy. Our main contribution is that we overcome the problems of previous studies such as: selection between hours and employment, lack of identi…cation strategy due to the joint implementation of policies and lack of crucial variables (like hourly wages and usual hours). Our results suggest no signi…cant e¤ects of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
12
0
2
Order By: Relevance
“…As emphasised in the Jobs Strategy, very long working hours impair the quality of the work environment, which is a key dimension through which work affects wellbeing (OECD, 2018 [1]). They increase the risk of work accidents, negatively affect worker health, and decrease hourly worker productivity, by increasing stress and fatigue while reducing the time available for recovery (Bassanini and Caroli, 2015 [7]; Saint-Martin, Inanc and Prinz, 2018 [8]). 6 This suggests that the high rate of fatal work injuries and low productivity performance in Korea may be linked to the high incidence of very long working hours.…”
Section: Very Long Working Hours Compromise Worker Health Productivimentioning
confidence: 99%
“…As emphasised in the Jobs Strategy, very long working hours impair the quality of the work environment, which is a key dimension through which work affects wellbeing (OECD, 2018 [1]). They increase the risk of work accidents, negatively affect worker health, and decrease hourly worker productivity, by increasing stress and fatigue while reducing the time available for recovery (Bassanini and Caroli, 2015 [7]; Saint-Martin, Inanc and Prinz, 2018 [8]). 6 This suggests that the high rate of fatal work injuries and low productivity performance in Korea may be linked to the high incidence of very long working hours.…”
Section: Very Long Working Hours Compromise Worker Health Productivimentioning
confidence: 99%
“…They found that small reductions in working hours resulted in small reductions in unemployment, whereas larger reduction of working hours resulted in increased unemployment. Sánchez (2013) wrote about the working hour reduction from 48 to 45 h per week implemented in Chile in 2005. He found that this reduction had no effect on unemployment.…”
Section: Working Hours In Other Scientific Literaturementioning
confidence: 99%
“…Then we will investigate (more extensively, as it is our main goal) the indirect effect of the regulation on health. Thus, in order to study the effect of the regulation on working hours we estimate the following regression (as in Sánchez ):Hoursit=italicβxit+italicα1g1i+italicα2g2i+italicγdt+italicδ1g1idt+italicδ2g2idt+italicεitwhere Hours refers to weekly working hours for individual i at period t , x it is a vector of covariates and does not include a constant. g ki d t represents the interaction variable between the time dummy ( d t ) and the group dummy ( g ki ) where k=1,2 represents the control and treatment group, respectively.…”
Section: Empirical Strategy and Estimationmentioning
confidence: 99%